Nilai-Nilai Nasionalisme Dalam Novel Cut Nyak Dhien Karya M.H. Skelely Lulofs - Yulsafli Yulsafli; Fusrida Fusrida (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
The novel revolves about a woman named Cut Nyak Dhien, who is often called